Endogenous and exogenous galectin-3 promote the adhesion of tumor cells with low expression of MUC1 to HUVECs through upregulation of N-cadherin and CD44. (December 2018) - Cao, Zhanqi; Hao, Zhaojun; Xin, Ming; Yu, Lugang; Wang, Lei; Zhang, Ying; Zhang, Xinke; Guo, Xiuli
Abstract Tumor cell-endothelial adhesion is one of the key steps in tumor cell haematogenous dissemination in metastasis and was previously shown to be mediated by interaction of galectin-3 with the transmembrane mucin protein MUC1. In this study, the effect of exogenous as well as endogenous galectin-3 on adhesion of two cell lines (low MUC1-expressing human prostate cancer PC-3M cells and non-small-cell lung cancer A549 cells) to monolayer of umbilical vein endothelial cells (HUVECs) was investigated. We found that suppression of endogenous galectin-3 expression reduced tumor cell adhesion to HUVECs and also decreased cell invasion and migration. Exogenous galectin-3 promoted tumor cell adhesion to HUVECs by entering cells. Both exogenous and endogenous galectin-3 upregulated the expression of β-catenin and increased β-catenin nuclear accumulation, and subsequently upregulated the expression of N-cadherin and CD44. We deduced that both exogenous as well as endogenous galectin-3 promoted low MUC1-expressing cancer cell adhesion to HUVECs by increasing the expression of N-cadherin and CD44 via an increase of nuclear β-catenin accumulation. These results were confirmed further by using a β-catenin/TCF transcriptional activity inhibitor, N-cadherin or CD44 siRNAs. Taken together, our results suggest a new molecular mechanism of galectin-3-mediated cell adhesion in cancer metastasis. Tumor cell-endothelial adhesion is one of the key steps for invasion and metastasis. The authors show that Gal-3 promotes cancer cell adhesion to vascular endothelial cells by increasing the expression of N-cadherin and CD44 via an increase of β-catenin nuclear accumulation. This new molecular mechanism of Gal-3-mediated cell adhesion may aid in the development of new strategies to prevent metastasis.